Measurement of astrophysical S-factors and electron screening potentials for View the MathML source reaction in ZrD2, TiD2 and TaD0.5 targets in the ultralow energy region using plasma accelerator; Nuclear Physics A; Vol. 889 - Bystritsky V. M.; Bystritskii Vit. M.; Dudkin G. N. Gennadiy Nikolaevich; Filipowicz M.; Gazi S.; Huran J.; Kobzev A. P.; Mesyats G. A. Gennady Andreyevich; Nechaev B. A. Boris Aleksandrovich; Padalko V. N. Vladimir Nikolaevich; Parzhitskii S. S.; Pen’kov F. M.; et al. (2012, 2012)
Title screen